Russell W. Peterson papers - Peterson, Russell W. (Russell Wilbur), 1916-2011.; Peterson, Russell W. (Russell Wilbur), 1916-2011.
Correspondence, speeches, writings, oral history transcript, subject files, trips and events files, and other papers relating primarily to Peterson's work as an environmentalist, chairman of the Council on Environmental Quality, president of New Directions, director of the Office of Technology Assessment of the U.S. Congress, and president of the National Audubon Society. Also documents Peterson's work for the presidential campaigns of Michael Dukakis and Bill Clinton, the Better World Society, and E.I. du Pont de Nemours & Company, and his participation in United Nations conferences on human settlement and population. Subjects include the Coastal Zone Act, crime prevention, criminal justice standards and goals, effects of environmental regulation on the economy, energy, environmental policies and records of the Gerald R. Ford and Ronald Reagan administrations, global issues, impact of science and technology, population stabilization, prevention of nuclear war, prison reform, protection of the global environment, quality of life, and reduction of world poverty. Includes drafts and related materials for Peterson's memoirs, Rebel with a conscience (1999).
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Governor of Delaware and environmentalist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Clinton, Bill, -- 1946-; Dukakis, Michael S. -- 1933-; Ford, Gerald R., -- 1913-2006.; Reagan, Ronald; United States. -- Congress. -- Office of Technology Assessment; Better World Society; Council on Environmental Quality (U.S.); E.I. du Pont de Nemours & Company; National Audubon Society; New Directions (Organization); United Nations; Antinuclear movement; Birds -- Conservation; Coastal zone management -- United States; Crime prevention; Criminal justice, Administration of; Energy consumption; Energy policy; Environmental law -- United States; Environmental policy -- United States; Environmental protection -- International cooperation; Environmentalism; Globalization; Human settlements -- Congresses; Nature conservation; Nuclear warfare; Ornithology; Population; Population -- Congresses; Poverty; Presidents -- United States -- Election -- 1988.; Presidents -- United States -- Election -- 1992.; Presidents -- United States -- Election -- 1996.; Prisons -- United States; Prison reformers -- United States; Quality of life; Science -- Social aspects; Technology -- Social aspects; Technology -- United States; United States -- Economic conditions -- 20th century; United States -- Economic policy -- 20th century; Conservationists; Governors -- Delaware